Higher stroke incidence in the patients with pancreatic cancer: A nation-based cohort study in Taiwan. Issue 11 (March 2018) - Chan, Po-Chi; Chang, Wei-Lun; Hsu, Min-Hsien; Yeh, Chung-Hsin; Muo, Chih-Hsin; Chang, Ko-Shih; Hsu, Chung Y.; Wu, Bor-Tsang; Lai, Ching-Hsiang; Lee, Ching-Hsiao; Ting, Hua; Sung, Fung-Chang
Abstract : Abstract: No study has investigated the role of pancreatic cancer in the stroke risk using population data. We used claims data obtained from a universal health insurance program of Taiwan to evaluate the stroke risk in pancreatic cancer patients. From the catastrophic disease registry of the insurance, we identified 7479 patients with pancreatic malignancy without stroke history from 2000 to 2009. The comparison cohort consisted of 29, 916 individuals identified from 1 million insured people without cancer and stroke history, matching with the cancer cohort by propensity score. We followed each selected individual until stroke was diagnosed or until being censored for death or withdrawal from insurance, or for a maximum of 3 follow-up years, or the end of 2011. The pancreatic cancer cohort had a 2.3-fold greater incident stroke than comparisons had (28.5 vs 12.3 per 1000 person-years), with an adjusted hazard ratio (aHR) of 2.74 (95% confidence interval (CI) = 2.31–3.24) after controlling for covariates, or a subdistribution hazard ratio (SHR) of 2.04 (95% CI = 1.74–2.40) accounting for the competing risk of deaths. During the follow-up period, stroke events occurred constantly in comparisons, but declined rapidly in the cancer cohort. The pancreatic cancer cohort had a stroke incidence of 46.6 per 1000 person-years within 6 months postdiagnosis, with an aHR of 4.37 (95% CI = 3.45–5.54) and a SHR of 3.87 (95% CI = 3.08–4.86), relative to comparisons. Our study suggests that patients with pancreatic cancer are at an elevated risk of stroke, patients deserve sufficient follow-up care, particularly in the first 6 months after the diagnosis of the cancer, and for those with comorbidities. Abstract : Supplemental Digital Content is available in the text